Asian intensive care research and education - Gomersall, Charles David (Journal of Emergency and Critical Care Medicine, 2018)
Collaboration in both research and education are crucial in advancing Intensive Care in Asia. Progress in collaborative research is already being made through the Asian Critical Care Clinical Trials group and national groups and in collaborative education through the BASIC Collaboration.